Intercultural communication in healthcare: a duel or a duet? - Harmsen, J.A.M. (Cahiers du Centre de Linguistique et des Sciences du Langage, 2022)
DUE TO WORLDWIDE MIGRATION, physicians in Europe and North America commonly encounter more patients from different ethnic origins and cultural backgrounds than did their predecessors; and this has had important implications for healthcare, not only in presenting physicians with a variety of formerly ‘exotic’ medical symptoms and diseases, but also presenting them with differences in the way patients view their needs and the expectations they bring to the clinical encounter (Kleinman et al., 1978). While the prevailing attitude of Western medicine has shifted over the last thirty years to a mostly patient-centred model, focused on shared decision-making (Cegala et al., 2000; Cecil & Killeen, 1997; Edwards et al., 2003), one may wonder how this model fits with the attitudes of patients coming from culturally different backgrounds (Kleinman, 1980; Pachter, 1994; Harmsen, 2003).